Evaluation of functional outcomes after a second focal high‐intensity focused ultrasonography (HIFU) procedure in men with primary localized, non‐metastatic prostate cancer: results from the HIFU Evaluation and Assessment of Treatment (HEAT) registry. (11th February 2020) - Lovegrove, Catherine E.; Peters, Max; Guillaumier, Stephanie; Arya, Manit; Afzal, Naveed; Dudderidge, Tim; Hosking‐Jervis, Feargus; Hindley, Richard G.; Lewi, Henry; McCartan, Neil; Moore, Caroline M.; Nigam, Raj; et al.
Abstract : Objectives: To assess change in functional outcomes after a second focal high‐intensity focused ultrasonography (HIFU) treatment compared with outcomes after one focal HIFU treatment. Patients and Methods: In this multicentre study (2005–2016), 821 men underwent focal HIFU for localized non‐metastatic prostate cancer. The patient‐reported outcome measures of International Prostate Symptom Score (IPSS), pad usage and erectile function (EF) score were prospectively collected for up to 3 years. To be included in the study, completion of at least one follow‐up questionnaire was required. The primary outcome was comparison of change in functional outcomes between baseline and follow‐up after one focal HIFU procedure vs after a second focal HIFU procedure, using IPSS, Expanded Prostate Cancer Index Composite (EPIC) and International Index of Erectile Function (IIEF) questionnaires. Results: Of 821 men, 654 underwent one focal HIFU procedure and 167 underwent a second focal HIFU procedure. A total of 355 (54.3%) men undergoing one focal HIFU procedure and 65 (38.9%) with a second focal HIFU procedure returned follow‐up questionnaires, respectively. The mean age and prostate‐specific antigen level were 66.4 and 65.6 years, and 7.9 and 8.4 ng/mL, respectively. After one focal HIFU treatment, the mean change in IPSS was −0.03 ( P = 0.02) and in IIEF (EF score) it was −0.4 ( P = 0.02) at 1–2 years, with no subsequent decline. Absolute rates of erectile dysfunction increased from 9.9% to 20.8% ( P = 0.08), leak‐free continence decreased from 77.9% to 72.8% ( P = 0.06) and pad‐free continence from 98.6% to 94.8% ( P = 0.07) at 1–2 years, respectively. IPSS prior to second focal HIFU treatment compared to baseline IPSS prior to first focal HIFU treatment was lower by −1.3 ( P = 0.02), but mean IPSS change was +1.4 at 1–2 years ( P = 0.03) and +1.2 at 2–3 years ( P = 0.003) after the second focal HIFU treatment. The mean change in EF score after the second focal HIFU treatment was −0.2 at 1–2 years ( P = 0.60) and −0.5 at 2–3 years ( P = 0.10), with 17.8% and 6.2% of men with new erectile dysfunction. The rate of new pad use was 1.8% at 1–2 years and 2.6% at 2–3 years. Conclusion: A second focal HIFU procedure causes minor detrimental effects on urinary function and EF. These data can be used to counsel patients with non‐metastatic prostate cancer prior to considering HIFU therapy.